Analysis of Learning Motivation of Junior Hight School Students in Terms of the use of Digital Platforms in Online Learning - Lesnawati, Delis; Suryawati, Evi; Suwondo, Suwondo (FKIP - Universitas Riau, 2022)
This study aims to analyze the level of motivation to learn science in terms of the use of platforms in online learning. The research was carried out at Junior Hight School (SMP) Negeri Singingi, Kuansing Regency, Indonesia for the 2021-2022 Academic Year. This research is quantitative descriptive. The type of data obtained consists of primary data and secondary data. The instrument used to measure the level of student learning motivation is using a questionnaire. This learning motivation questionnaire was prepared with reference to the aspect of learning motivation which consists of 8 aspects. The results of learning motivation on the concentration indicator get an average of 64.56% in the medium category, the curiosity indicator on average 64.83% in the medium category, the average spirit indicator 62.14% in the medium category, the average independence indicator at 70.25% in the high category, the average readiness indicator is 77.50% in the high category, the average enthusiasm and encouragement indicator is 64.68% in the medium category, the indicator of never giving up is on average 66.67% in the medium category, and the average confidence indicator is 79.18% in the high category. The results of the study concluded that the overall student learning motivation was categorized as good.